GLUTATHION MENINGKATKAN KUALITAS TUBULUS SEMINIFERUS PADA MENCIT YANG MENERIMA PELATIHAN FISIK BERLEBIH - Laksmi, Desak Nyoman Indira (Buletin Veteriner Udayana, 2012)
The aims of this study was to find out influence of glutathione on tubuleseminiferous quality during the overtraining. This study was experimentally and randomlypretest-posttest with control group design. The samples of this study were strain Balb-Cadult male mice with the following criteria: body weight between 20-25 grams, age 2-3months, randomly, 48 mice were divided into two groups, 24 mice were control group andthe other 24 were treatment group (Po = physical overtraining group with aqua proinjection,intraperitoneal, and P1 = physical overtraining group with glutathione 6 Mmol/kg. BW/day, intra-peritoneal). Prior to the treatment, 12 mice were taken from each group forthe pre-test, by preparing microscopic preparation testicle and examination was performedto seminiferous tubules quality. The rests of the mice, 12 mice were used as for post-testexamination after 35 days treatment. The result showed that the quality of seminiferoustubules significantly increase (p<0, 05) after the glutathione treatment. It can be concludedthat the glutathione treatment improved the quality of seminiferous tubules.
Keywords: Physical overtraining; glutathione; seminiferous tubules quality